The Significant Role of Tumor Volume on the Surgical Approach Choice, Surgical Complexity, and Postoperative Complications in Renal Cell Carcinoma With Venous Tumor Thrombus From a Large Chinese Center Experience - Baheen, Qais; Liu, Zhuo; Hao, Yichang; Sawh, Rejean R. R.; Li, Yuxuan; Zhao, Xun; Hong, Peng; Wu, Zonglong; Ma, Lulin (Frontiers in Oncology, 2022)
Objective: To explore the role of tumor volume (TV) on surgical approach choice, surgical complexity and postoperative complications in patients with renal cell carcinoma (RCC) and inferior vena cava tumor thrombus. Method: From January 2014 to January 2020, we retrospectively analyzed the clinical data of 132 patients who underwent radical nephrectomy with inferior vena cava thrombectomy (RN-IVCT). Primary renal tumor volume (PRTV), renal vein tumor thrombus volume (RVTTV), inferior vena cava tumor thrombus volume (IVCTTV), and total tumor thrombus volume (TTTV) were measured with the help of an internationally recognized 3D volume measurement software. The patients were divided into three groups according to the tumor volume within inferior vena cava (IVC). Group 1 included 48 patients with IVCTTV between 0-15 cm3 (36.6%), group 2 included 38 patients with IVCTTV between 16-30 cm3 (28%), and group 3 included 46 patients with IVCTTV above 30 cm3 (35%). The three IVCTTV groups, as well as four different volume groups, were compared in term of surgical approach choice, surgical complexity and postoperative complications. One-way ANOVA and nonparametric test were used to compare the clinicopathological characteristics and distribution differences between the three groups. Result: This study found significant differences among the three groups in the proportion of open surgery (P < 0.001), operation time (P < 0.044), intraoperative bleeding (P < 0.001) and postoperative complications (P < 0.001). When compared the four different volumes, we found that for higher volume IVCTTV and TTTV, open surgery is used more often compared with laparoscopic (32 vs 14, P < 0.001). In addition, with the increase of renal vein tumor thrombus volume, inferior vena cava tumor thrombus volume and total tumor thrombus volume, the operation time also increased. And finally, with the increase of tumor thrombus volume and total tumor thrombus volume, the amount of intraoperative bleeding increased. Conclusion: With the increase of tumor volume, the proportion of open surgery and the incidence of postoperative complications increased. In addition, larger tumor volume prolongs operation time, increases intraoperative blood loss, and makes the surgery more complicated.